Saúde bucal de pacientes com Síndrome de Prader-Willi: um estudo observacional caso-controle - Costa, Janaina Ferreira da (2025)
Prader-Willi syndrome (PWS) is a rare and multisystemic genetic condition associated with endocrine, cognitive, behavioral, and oral alterations. This study aimed to assess the caries index and gingival health of individuals with PWS, compared to a non- syndromic control group matched by age and sex. This was an observational case- control study. The sample consisted of 24 participants equally divided between the PWS group (n=12) and the control group (n=12), including 7 females and 5 males aged between 5 and 20 years. Clinical examination and anamnesis were conducted to collect systemic, behavioral, and dental information. Caries experience was assessed using the DMFT/dmft index, and gingival health using the Plaque Index and Gingival Index by Löe and Silness. Data were analyzed using descriptive statistics and comparative tests (Fisher’s exact test, Mann-Whitney test), with a significance level of 5%. Results showed a higher DMFT in the PWS group compared to the control group (6.67±4.33 vs. 3.33±3.55; p = 0.042), while no statistically significant differences were found in plaque (p = 0.840) and gingival indices (p = 0.094). In the PWS group, there was a relevant presence of systemic conditions (diabetes, autism, intellectual disability), as well as enamel defects and tooth wear. Correlations among clinical, systemic, and behavioral characteristics revealed a statistically significant association between intellectual disability and lack of dental visits (p = 0.025). In conclusion, individuals with PWS showed greater caries experience, highlighting the need for specialized and preventive dental care. Although no significant differences were found in gingival and plaque indices, the systemic conditions, enamel defects, tooth wear, and behavioral aspects observed reinforce the multifactorial impact on the oral health of these patients. These findings support the importance of individualized and integrated care strategies in the dental management of individuals with PWS.